A low-calcium, high-sulfur silicate cement clinker and its preparation method and application

By using low-calcium and high-sulfur silicate cement clinker, high-active α' type dicalcium silicate, β-type dicalcium silicate, calcium sulfate and other minerals, the high CO2 emission and early intensity of silicate cement clinker are solved. The problem of low carbon emissions and high-strength cement production has been achieved.

CN118878227BActive Publication Date: 2025-02-18HEBEI UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411364501.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2024-07-09
Filing Date
2024-09-29
Publication Date
2025-02-18
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

The existing silicate cement clinker has high CO2 emissions during the production process, and the early strength of high Bellet silicate cement is low, making it difficult to replace traditional silicate cement.

Method used

Use low-calcium high-sulfur silicate cement clinker, whose mineral components include high-active α' type dicalcium silicate and solid-solution sulfur trioxide highly active β-type dicalcium silicate. Calcium sulfate exists in amorphous form, through High temperature calcination forms highly active minerals and improves hydration activity.

Benefits of technology

It significantly reduces CO2 emissions, increases the early strength and later strength development of high-Belite silicate cement, and is suitable for construction, transportation, water conservancy and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118878227B_ABST
    Figure CN118878227B_ABST
Patent Text Reader

Abstract

The present invention provides a low-calcium, high-sulfur silicate cement clinker and a preparation method and application thereof. The mineral components of the low-calcium, high-sulfur silicate cement clinker include dicalcium silicate and calcium sulfate, and the sum of the masses of the two is not less than 68% of the total mass of the silicate cement clinker. At the same time, the mass ratio of calcium sulfate to dicalcium silicate is not less than 0.13. The present invention also provides various cements prepared based on the low-calcium, high-sulfur silicate cement clinker, and methods for preparing the low-calcium, high-sulfur silicate cement clinker and the cement. The low-calcium, high-sulfur silicate cement clinker of the present invention has the advantages of high early strength, continuous growth in late strength, and low CO2 emissions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of inorganic building materials, and specifically relates to a low-calcium and high-sulfur silicate cement clinker and a preparation method and application thereof. Background Art

[0002] Cement is an indispensable raw material for infrastructure construction and plays an important role in national economic construction. The raw materials for the production of silicate cement are cheap and easy to obtain, the performance is stable, and the production process is mature. It is one of the most widely used inorganic cementitious materials. However, silicate cement consumes a lot of natural resources and emits high CO2 during the production process. The production of 1 ton of silicate cement clinker emits about 0.87 tons of CO2. At present, the global cement production has exceeded 4 billion tons, and the CO2 emitted by its production accounts for about 7% of the global total. In the cement low-carbon technology roadmap released by the International Energy Agency, the carbon emission reduction potential in the clinker production stage is 34%, and the carbon emission reduction potential of cement performance improvement in the application stage is 10%. Therefore, it is urgent to develop a new type of low-carbon cement clinker to replace traditional silicate cement clinker on a large scale.

[0003] Portland cement clinker is usually composed of 40%~60% tricalcium silicate, 15%~35% dicalcium silicate, 5%~14% tricalcium aluminate and 10%~16% tetracalcium aluminoferrite. The order of CO2 emission from clinker minerals is tricalcium silicate> tricalcium aluminate> dicalcium silicate> tetracalcium aluminoferrite. One of the effective ways to reduce the CO2 emission of Portland cement clinker is to reduce the content of tricalcium silicate and correspondingly increase the content of low-calcium mineral dicalcium silicate. However, dicalcium silicate in Portland cement clinker is mainly β-type, and its activity is much lower than that of tricalcium silicate. High-belite Portland cement with dicalcium silicate as the main mineral has problems such as low early strength and slow later strength development. Although ion doping and other means can be used to change the crystal structure of dicalcium silicate and thus improve its activity, the early strength of high-belite Portland cement after activation is still difficult to reach the level of traditional Portland cement.

[0004] Therefore, it is necessary to develop a new cement clinker that not only has lower carbon emissions but also can produce silicate cement products with higher early strength. Summary of the invention

[0005] The primary purpose of the present invention is to provide a new cement clinker which not only has low carbon emission but also can provide higher early strength for Portland cement.

[0006] Another object of the present invention is to provide a method for preparing the cement clinker.

[0007] Another object of the present invention is to provide application of the cement clinker in preparing building materials.

[0008] The above-mentioned object of the present invention is achieved by the following technical solutions:

[0009] In a first aspect, the present invention provides a low-calcium, high-sulfur Portland cement clinker, whose mineral components include dicalcium silicate and calcium sulfate, and the sum of the masses of the two is not less than 68% of the total mass of the Portland cement clinker, preferably not less than 73%, and further preferably not less than 79%; at the same time, the mass ratio of calcium sulfate to dicalcium silicate is not less than 0.13, preferably not less than 0.26, and further preferably not less than 0.33.

[0010] In the low-calcium and high-sulfur Portland cement clinker of the present invention, the dicalcium silicate is preferably a mixture of highly active α'-type dicalcium silicate and highly active β-type dicalcium silicate dissolved with sulfur trioxide.

[0011] In the low-calcium, high-sulfur Portland cement clinker of the present invention, the calcium sulfate portion preferably exists in an amorphous form.

[0012] In the preferred low-calcium and high-sulfur Portland cement clinker of the present invention, the dicalcium silicate content is 49% to 81% by weight, more preferably 53% to 77%, and further preferably 57% to 73%.

[0013] In the preferred low-calcium high-sulfur Portland cement clinker of the present invention, the calcium sulfate content is 8% to 26% by weight, more preferably 11% to 23%, and further preferably 14% to 20%.

[0014] In the preferred low-calcium, high-sulfur Portland cement clinker of the present invention, the mineral component further comprises anhydrous calcium sulphoaluminate; in the low-calcium, high-sulfur Portland cement clinker, the content of anhydrous calcium sulphoaluminate is 5% to 25% by weight, preferably 10% to 25%, and further preferably 10% to 20%.

[0015] In the preferred low-calcium, high-sulfur Portland cement clinker of the present invention, the mineral components further include an iron phase; in terms of weight percentage, the iron phase content in the low-calcium, high-sulfur Portland cement clinker is 1%-15%.

[0016] In the further preferred low-calcium high-sulfur Portland cement clinker of the present invention, the mineral component also contains free calcium oxide; in terms of weight percentage, the content of free calcium oxide is 0.01% to 3.9% of the total weight of the low-calcium high-sulfur Portland cement clinker.

[0017] The mineral content of the above-mentioned low-calcium, high-sulfur silicate cement clinker is obtained by theoretical calculation based on the oxide content in the clinker.

[0018] In the low-calcium high-sulfur Portland cement clinker described in the present invention, the essential components include dicalcium silicate and calcium sulfate. Among them, the mechanism of action of calcium sulfate includes: ① calcium sulfate exists in liquid form at high temperature, which can accelerate the diffusion rate of reactants, promote the formation of clinker minerals such as dicalcium silicate, and reduce the clinker burning temperature, thereby significantly reducing the clinker CO2 emission. ② During the clinker burning process, dicalcium silicate and calcium sulfate will react to form calcium sulfosilicate. As the temperature further increases, calcium sulfosilicate will decompose into amorphous calcium sulfate, highly active α'-type dicalcium silicate and highly active β-type dicalcium silicate with solid solution of sulfur trioxide. These two types of dicalcium silicates have high hydration activity, which solves the problem of low early strength of high-belite Portland cement. ③ During the cooling of the clinker, the liquid phase formed by calcium sulfate is conducive to stabilizing the highly active α'-type dicalcium silicate. In addition, in the preparation process of traditional Portland cement clinker, calcium and aluminum usually react to form tricalcium aluminate. In the present invention, in the presence of calcium sulfate, calcium, aluminum and calcium sulfate will react to form anhydrous calcium sulfoaluminate. Anhydrous calcium sulphoaluminate has high early hydration activity, which can further ensure the development of early strength of high belite silicate cement.

[0019] The mechanism of action of free calcium oxide in the preferred low-calcium high-sulfur Portland cement clinker of the present invention mainly includes: the free calcium oxide in the clinker of the present invention is calcined at a low temperature of 1250±100°C and has high activity. The free calcium oxide in the clinker can be used to regulate the dissolution rate of minerals such as anhydrous calcium sulfoaluminate, calcium sulfate and dicalcium silicate, as well as the precipitation rate of hydration products such as ettringite, thereby regulating the coagulation and hardening rate of the clinker.

[0020] In a second aspect, the present invention also provides a method for preparing the low-calcium high-sulfur silicate cement clinker described in the first aspect, comprising: grinding and homogenizing a mixed raw material containing silicon, aluminum, sulfur, calcium and iron elements according to the content of each mineral component of the low-calcium high-sulfur silicate cement clinker described in the first aspect, and then subjecting the mixed raw material to a high-temperature reaction to obtain the low-calcium high-sulfur silicate cement clinker. Preferably, the high-temperature reaction is high-temperature calcination; more preferably, the temperature of the high-temperature calcination is 1250°C ± 100°C; and further preferably, the temperature of the high-temperature calcination is 1250°C ± 50°C.

[0021] In the method for preparing the low-calcium high-sulfur silicate cement clinker described in the first aspect of the present invention, the mixed raw material containing silicon, aluminum, sulfur, calcium and iron elements is any one of a plurality of compositions composed of a plurality of substances selected from limestone, alkali slag, steel slag, carbide slag, bauxite, high-iron bauxite, garbage fly ash, red mud, aluminum ash, bauxite tailings, coal gangue, kaolin, boiling furnace slag, clay, sandstone, natural anhydrous gypsum, natural dihydrate gypsum, desulfurized gypsum, semi-hydrated gypsum, phosphogypsum, fluorite, desulfurized ash, aluminum sulfate, industrial waste rich in gypsum, iron ore, selected iron ore powder, fly ash, granulated blast furnace slag or gasified slag. Preferably, the mixed raw material containing silicon, aluminum, sulfur, calcium and iron elements is composed of limestone, steel slag, fly ash, desulfurized gypsum, phosphogypsum and sandstone.

[0022] The method for preparing the clinker of the present invention is similar to the method for preparing conventional silicate cement clinker, and can be industrially produced using conventional silicate cement clinker production lines. However, the advantages of the preparation method of the present invention are: low sintering temperature and low requirements on raw material quality.

[0023] In a third aspect, the present invention also provides the following various cements prepared based on the low-calcium, high-sulfur silicate cement clinker described in the first aspect of the present invention.

[0024] An early strength cement is prepared from the following raw materials, measured by weight: 80-100 parts of the low-calcium and high-sulfur silicate cement clinker described in the first aspect of the present invention, 0-20 parts of gypsum, and 0-20 parts of cement admixture.

[0025] A high-strength cement is prepared from the following raw materials, measured by weight: 50-80 parts of the low-calcium high-sulfur silicate cement clinker described in the first aspect of the present invention, 0-20 parts of gypsum, and 20-50 parts of cement admixture.

[0026] A cement with low hydration heat characteristic is prepared from the following raw materials, measured by weight: 5-50 parts of the low-calcium high-sulfur silicate cement clinker described in the first aspect of the present invention, 0-20 parts of gypsum, and 50-95 parts of cement admixture.

[0027] Any one of the early-strength cement, high-strength cement or cement with low hydration heat characteristics described in the present invention, the gypsum in its raw material is any one of natural dihydrate gypsum, natural anhydrite, hemihydrate gypsum, α-type high-strength gypsum, desulfurized gypsum, phosphogypsum or fluorinated gypsum, or a combination of at least two of them; preferably, the gypsum is any one of natural dihydrate gypsum, natural anhydrite, hemihydrate gypsum, desulfurized gypsum, or a combination of at least two of them.

[0028] Any one of the early strength cement, high strength cement or cement with low hydration heat characteristics described in the present invention, the cement admixture described in its raw materials is any one of granulated blast furnace slag, fly ash, silica fume, steel slag, gasified slag, limestone, dolomite, volcanic ash mixed material or sandstone, or a combination of at least two of them.

[0029] The raw materials of any one of the early strength cement, high strength cement or cement with low hydration heat characteristics preferably used in the present invention may further include 0.1 to 5 parts by weight of a setting and strengthening component.

[0030] The setting and strengthening component is selected from any one of lithium hydroxide, sodium hydroxide, potassium hydroxide, lithium sulfate, sodium sulfate, potassium sulfate, aluminum sulfate, lithium carbonate, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, sodium silicate, lithium chloride, citric acid, sodium citrate or sodium gluconate, or a combination of at least two of them; preferably, the setting and strengthening component includes any one of lithium hydroxide, sodium hydroxide, lithium sulfate, sodium sulfate, aluminum sulfate, lithium carbonate, citric acid, sodium citrate or sodium gluconate, or a combination of at least two of them; more preferably, the setting and strengthening component also includes any one of silicate cement, silicate cement clinker, quicklime, slaked lime, industrial calcium oxide, industrial calcium hydroxide, carbide slag, calcium oxide expansion agent, and calcium sulfonate expansion agent, or a combination of at least two of them.

[0031] In a fourth aspect, the present invention also provides a method for preparing any of the above cements, comprising: mixing the raw materials according to the raw material ratio of any of the above cements and grinding the raw materials together into a cement having a specific surface area of ​​200 to 800 m 2 / g of powder to obtain the cement; preferably, the raw materials are mixed and ground together to a specific surface area of ​​300 to 600 m 2 / g powder to obtain the cement; or grind each raw material separately to a specific surface area of ​​200 to 1000 m 2 / g of powder, and then mixing to obtain the cement.

[0032] In a fifth aspect, the present invention also provides the use of the low-calcium, high-sulfur silicate cement clinker described in the first aspect of the present invention in the preparation of building materials.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] The present invention innovatively uses dicalcium silicate and calcium sulfate as the main minerals to prepare silicate cement clinker. Dicalcium silicate and calcium sulfate first react to form calcium sulfosilicate in a high-temperature process. As the temperature further increases, calcium sulfosilicate decomposes into amorphous calcium sulfate, highly active α'-type dicalcium silicate and highly active β-type dicalcium silicate with solid solution of sulfur trioxide. This process greatly improves the hydration activity of dicalcium silicate and calcium sulfate, ensuring the early strength and late strength development of high-belite silicate cement. Calcium sulfate can also react rapidly with another highly active mineral anhydrous calcium sulfoaluminate and water in the clinker to further improve the early strength. In addition, calcium sulfate exists in liquid form at high temperatures, which can not only stabilize the highly active crystal form of dicalcium silicate, but also accelerate the diffusion rate of reactants, promote the formation of clinker minerals, and reduce the clinker burning temperature (about 200°C lower than traditional silicate cement clinker). Therefore, compared with the existing high-belite silicate cement clinker, the low-calcium and high-sulfur silicate cement clinker of the present invention has the advantages of high early strength, continuous growth in late strength, and low CO2 emissions. This clinker can be used to prepare cement with characteristics such as early strength, high strength, and low hydration heat, and is suitable for use in the fields of construction, transportation, water conservancy, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is the X-ray diffraction spectrum of the low-calcium and high-sulfur silicate cement clinker of the present invention and the traditional silicate cement clinker. DETAILED DESCRIPTION

[0036] The scheme and technical effects of the present invention are further described in detail below by listing examples and comparative examples. However, the examples listed should not be construed as limiting the scheme of the present invention.

[0037] The present invention relates to the correspondence between the Chinese names and chemical symbols of mineral components: dicalcium silicate (C2S), calcium sulfate (CaSO4), anhydrous calcium sulfoaluminate (C4A3S̅), iron phase (C4AF), perovskite (CT), free calcium oxide (f-CaO).

[0038] The mineral composition of the clinker in the present invention is calculated based on the oxide composition:

[0039] w(C4A3S̅)=1.99[w(Al2O3)-0.64w(Fe2O3)]

[0040] w(C2S)=2.87w(SiO2)

[0041] w(C4AF)=3.04w(Fe2O3)

[0042] w(CaSO4)=1.7[w(SO3)-0.13w(C4A3S̅)]

[0043] w(CT)=1.7w(TiO2)

[0044] w(f-CaO)=w(CaO)-0.55[w(Al2O3)-0.64w(Fe2O3)]-1.87w(SiO2)-1.4w(Fe2O3)-0.7[w(TiO2)+w(SO3)]

[0045] The amorphous phase composition in the clinker of the present invention is inferred based on oxide calculation results and X-ray diffraction (XRD) test results.

[0046] Example 1-Example 25

[0047] A series of low-calcium and high-sulfur silicate cement clinkers were prepared, and the raw materials included limestone, fly ash, desulfurized gypsum and sandstone; the chemical composition of each raw material is shown in Table 1 below:

[0048] Table 1: Chemical composition of raw materials required to produce low calcium and high sulfur Portland cement clinker

[0049]

[0050] The raw materials in Table 1 were mixed according to the proportions listed in Table 2 and ground to less than 80 μm. After homogenization, the raw materials were calcined at a high temperature of 1250° C. to obtain a series of low-calcium and high-sulfur silicate cement clinkers of Examples 1 to 25.

[0051] Table 2: Raw material ratios used to produce low calcium high sulfur silicate cement clinker of Examples 1-25

[0052]

[0053] The chemical composition and mineral composition of the above series of clinkers were analyzed. The mineral composition was calculated by chemical composition. The results are shown in Table 3 below:

[0054] Table 3: Chemical and mineral compositions of low calcium high sulfur Portland cement clinkers of Examples 1-25

[0055]

[0056] The mineral composition of the low calcium and high sulfur Portland cement clinker of Example 10 was characterized by XRD. The XRD spectrum is shown in FIG. Figure 1 The quantitative analysis results are shown in Table 4. Figure 1 The blue curve represents the low calcium and high sulfur Portland cement clinker of Example 10, and the red curve represents the traditional Portland cement clinker. Figure 1It can be seen that in addition to the diffraction peaks corresponding to dicalcium silicate, calcium sulfate and anhydrous calcium sulfoaluminate, the blue curve also has an obvious "mantou peak", indicating that the low-calcium and high-sulfur silicate cement clinker contains a large amount of amorphous phase. As can be seen from Table 4, dicalcium silicate mainly exists in the highly active α' type. In addition, the XRD measured values ​​of calcium sulfate and dicalcium silicate are lower than the XRF calculated values, from which it can be inferred that a large amount of calcium sulfate and part of dicalcium silicate exist in amorphous form.

[0057] Table 4: Calculated and measured values ​​of mineral composition of low calcium and high sulfur Portland cement clinker of Example 10

[0058]

[0059] The physical and mechanical properties of a series of clinkers of Examples 1 to 25 were measured according to GB / T 1346 "Test Methods for Standard Water Consumption, Setting Time and Stability of Cement" and GB / T 17671 "Test Methods for Cement Mortar Strength (ISO Method)". The results are shown in Table 5:

[0060] Table 5: Physical and mechanical properties of low calcium high sulfur Portland cement clinker of Examples 1-25

[0061]

[0062] It can be seen from Table 5 that the strength and setting time of clinker are mainly determined by the mass ratio of calcium sulfate to dicalcium silicate and the mass sum. Generally speaking, the larger the mass ratio of the two, the smaller the mass sum, the faster the setting and hardening rate of the clinker, and the higher the flexural strength and compressive strength.

[0063] Comparative Example 1-Comparative Example 5

[0064] Table 6: Chemical and mineral compositions of low calcium silicate cement clinkers of Comparative Examples 1-5

[0065]

[0066] According to GB / T 1346 "Standard water consumption, setting time and stability test method for cement" and GB / T 17671 "Test method for strength of cement mortar (ISO method)", the physical and mechanical properties of a series of clinkers of Comparative Examples 1 to Comparative Examples 5 were measured, and the test results are shown in Table 7:

[0067] Table 7: Physical and mechanical properties of low calcium silicate cement clinker of Comparative Examples 1-5

[0068]

[0069] It can be seen from Table 7 that if the mass ratio of calcium sulfate to dicalcium silicate is lower than 0.13, the setting and hardening rate of low-calcium and high-sulfur silicate cement clinker will be slowed down, and the flexural strength and compressive strength will be significantly reduced.

[0070] Example 26-Example 30

[0071] A series of low calcium and high sulfur Portland cement clinkers with different free calcium oxide contents were prepared, and their chemical and mineral compositions are shown in Table 8 below:

[0072] Table 8: Chemical and mineral compositions of low calcium high sulfur Portland cement clinkers of Examples 26-30

[0073]

[0074] The physical and mechanical properties of a series of clinkers in Examples 26 to 30 were measured according to GB / T 1346 "Test Methods for Standard Water Consumption, Setting Time and Stability of Cement" and GB / T 17671 "Test Methods for Cement Mortar Strength (ISO Method)". The results are shown in Table 9:

[0075] Table 9: Physical and mechanical properties of low calcium high sulfur Portland cement clinker of Examples 26-30

[0076]

[0077] As can be seen from Table 9, with the increase of free calcium oxide content, the setting time of low-calcium high-sulfur Portland cement clinker shows a trend of first shortening and then extending, which shows that a small amount of free calcium oxide can accelerate the setting and hardening rate of clinker, while excessive free calcium oxide content will slow down the setting and hardening rate. In addition, free calcium oxide has a greater impact on the 6-hour strength of low-calcium high-sulfur Portland cement clinker, and a smaller impact on the 3-day and 28-day strength.

[0078] Example 31-Example 37

[0079] A series of early strength low calcium high sulfur Portland cements were prepared by using the clinker of Example 10 and one or more of anhydrite, slag, gasified slag or aluminum sulfate as raw materials. The specific raw material proportions are shown in Table 10 below:

[0080] Table 10: Raw material ratio of early strength low calcium high sulfur silicate cement

[0081]

[0082] According to GB / T 17671 "Test Method for Cement Mortar Strength (ISO Method)", the physical and mechanical properties of a series of early strength low calcium high sulfur silicate cements of Examples 31 to 37 were measured. The measurement results are shown in Table 11:

[0083] Table 11: Mechanical properties of early strength low calcium high sulfur Portland cement of Examples 31-37

[0084]

[0085] It can be seen from Table 11 that with the increase of anhydrite content, the strength of early-strength low-calcium high-sulfur silicate cement shows a trend of first increasing and then decreasing. The addition of an appropriate amount of aluminum sulfate, a setting and strength-promoting component, is beneficial to the development of early and late strength.

[0086] Example 38-Example 45

[0087] A series of high-strength, low-calcium, high-sulfur silicate cements were prepared by using the clinker of Example 5 and one or more of anhydrite, slag, calcined clay, limestone powder or sodium sulfate as raw materials. The specific raw material proportions are shown in Table 12 below:

[0088] Table 12: Raw material ratio of high strength, low calcium and high sulfur Portland cement

[0089]

[0090] According to GB / T 17671 "Test Method for Cement Mortar Strength (ISO Method)", the physical and mechanical properties of a series of high-strength, low-calcium, high-sulfur silicate cements of Examples 38 to 45 were measured. The results are shown in Table 13:

[0091] Table 13: Mechanical properties of high strength low calcium high sulfur Portland cement of Examples 38-45

[0092]

[0093] As can be seen from Table 13, reducing the clinker content in cement and correspondingly increasing the amount of admixtures is not conducive to the early strength development of high-strength, low-calcium, high-sulfur silicate cement, but promotes the later strength development. Adding an appropriate amount of sodium sulfate, a setting and strengthening component, can promote the early and later strength development. Adding a small amount of limestone powder can promote the strength development of cement, but too much limestone powder has an adverse effect on strength.

[0094] Example 46-Example 53

[0095] A series of low-calorie, low-calcium, high-sulfur silicate cements were prepared by using the clinker of Example 18 and one or more of anhydrite, slag, fly ash or citric acid as raw materials. The specific raw material proportions are shown in Table 14 below:

[0096] Table 14: Raw material ratio of low heat, low calcium and high sulfur Portland cement

[0097]

[0098] According to GB / T 17671 "Test Method for Cement Mortar Strength (ISO Method)", the physical and mechanical properties of a series of low-heat, low-calcium, high-sulfur silicate cements of Examples 46 to 53 were measured. The results are shown in Table 15:

[0099] Table 15: Physical and mechanical properties of low heat, low calcium, high sulfur Portland cement of Examples 46-53

[0100]

[0101] It can be seen from Table 15 that the hydration heat release and strength of low-heat, low-calcium, high-sulfur Portland cement decrease with the increase of fly ash content. Increasing the clinker content increases the hydration heat release and early strength of cement, but has little effect on the later strength.

Claims

1. A low calcium high sulfur silicate cement clinker, characterized in that: Its mineral components include dicalcium silicate and calcium sulfate. Calculated by weight, the content of dicalcium silicate is 49% to 81%, and the sum of the masses of the two is not less than 68% of the total mass of the silicate cement clinker; at the same time, the mass ratio of calcium sulfate to dicalcium silicate is not less than 0.13; the dicalcium silicate is a mixture of high-activity α'-type dicalcium silicate and high-activity β-type dicalcium silicate dissolved in sulfur trioxide.

2. The low-calcium, high-sulfur silicate cement clinker according to claim 1, characterized in that: The sum of the masses of the dicalcium silicate and calcium sulfate is not less than 73% of the total mass of the silicate cement clinker; at the same time, the mass ratio of the calcium sulfate to the dicalcium silicate is not less than 0.

26.

3. The low-calcium, high-sulfur silicate cement clinker according to claim 1, characterized in that: The sum of the masses of the dicalcium silicate and calcium sulfate is not less than 79% of the total mass of the silicate cement clinker; at the same time, the mass ratio of the calcium sulfate to the dicalcium silicate is not less than 0.

33.

4. The low-calcium, high-sulfur Portland cement clinker according to any one of claims 1 to 3, characterized in that: The calcium sulfate part exists in amorphous form.

5. The low-calcium, high-sulfur Portland cement clinker according to any one of claims 1 to 3, characterized in that: Calculated by weight, the content of dicalcium silicate is 53%~77%.

6. The low-calcium, high-sulfur Portland cement clinker according to any one of claims 1 to 3, characterized in that: Calculated by weight percentage, the content of dicalcium silicate is 57%~73%.

7. The low-calcium, high-sulfur Portland cement clinker according to any one of claims 1 to 3, characterized in that: By weight percentage, the calcium sulfate content is 8%~26%.

8. The low-calcium, high-sulfur Portland cement clinker according to any one of claims 1 to 3, characterized in that: By weight percentage, the calcium sulfate content is 11%~23%.

9. The low-calcium, high-sulfur Portland cement clinker according to any one of claims 1 to 3, characterized in that: By weight percentage, the calcium sulfate content is 14%~20%.

10. The low-calcium, high-sulfur Portland cement clinker according to any one of claims 1 to 3, characterized in that: The mineral component also contains anhydrous calcium sulphoaluminate; the content of anhydrous calcium sulphoaluminate is 5% to 25% by weight.

11. The low-calcium, high-sulfur Portland cement clinker according to claim 10, characterized in that: Calculated by weight percentage, the content of anhydrous calcium sulphoaluminate is 10% to 25%.

12. The low-calcium, high-sulfur Portland cement clinker according to claim 10, characterized in that: Calculated by weight percentage, the content of anhydrous calcium sulphoaluminate is 10% to 20%.

13. The low-calcium, high-sulfur Portland cement clinker according to any one of claims 1 to 3, characterized in that: The mineral components also contain an iron phase; in terms of weight percentage, the iron phase content in the low-calcium, high-sulfur silicate cement clinker is 1%-15%.

14. The low-calcium, high-sulfur Portland cement clinker according to any one of claims 1 to 3, characterized in that: The mineral component also contains free calcium oxide; in terms of weight percentage, the free calcium oxide content is 0.01% to 3.9% of the total weight of the low-calcium, high-sulfur silicate cement clinker.

15. A method for preparing the low-calcium, high-sulfur Portland cement clinker according to any one of claims 1 to 14, comprising: According to the content of each mineral component of the low-calcium high-sulfur silicate cement clinker according to any one of claims 1-14, a mixed raw material containing silicon, aluminum, sulfur, calcium and iron elements is ground and homogenized and then calcined at a high temperature of 1250°C±100°C to obtain the low-calcium high-sulfur silicate cement clinker.

16. The method according to claim 15, characterized in that: The temperature of the high temperature calcination is 1250°C±50°C.

17. The method according to claim 15, characterized in that: The mixed raw material containing silicon, aluminum, sulfur, calcium and iron elements is any one of a variety of compositions composed of various substances selected from limestone, alkali slag, steel slag, carbide slag, bauxite, garbage fly ash, red mud, aluminum ash, bauxite tailings, coal gangue, boiling furnace slag, clay, sandstone, natural anhydrous gypsum, natural dihydrate gypsum, desulfurized gypsum, hemihydrate gypsum, phosphogypsum, fluorinated gypsum, desulfurized ash, aluminum sulfate, iron ore, selected iron ore powder, fly ash, granulated blast furnace slag or gasified slag.

18. The method according to claim 15, wherein: The mixed raw material containing silicon, aluminum, sulfur, calcium and iron elements is composed of limestone, steel slag, fly ash, desulfurized gypsum, phosphogypsum and sandstone.

19. Application of low calcium high sulfur silicate cement clinker, characterized by: A composition comprising the low-calcium, high-sulfur silicate cement clinker described in any one of claims 1 to 14 and one or more of gypsum, cement admixtures and setting and strengthening components.

20. An early strength cement, prepared from the following raw materials, by weight: 80-100 parts of the low-calcium, high-sulfur silicate cement clinker according to any one of claims 1 to 14, 0-20 parts of gypsum, and 0-20 parts of cement admixture.

21. A high-strength cement prepared from the following raw materials, measured by weight: 50-80 parts of the low-calcium, high-sulfur silicate cement clinker according to any one of claims 1 to 14, 0-20 parts of gypsum, and 20-50 parts of cement admixture.

22. A cement with low hydration heat characteristics, prepared from the following raw materials, by weight: 5-50 parts of the low-calcium, high-sulfur silicate cement clinker according to any one of claims 1 to 14, 0-20 parts of gypsum, and 50-95 parts of cement admixture.

23. The cement according to any one of claims 20 to 22, characterized in that: The gypsum is any one of natural dihydrate gypsum, natural anhydrite, hemihydrate gypsum, α-type high-strength gypsum, desulfurized gypsum, phosphogypsum or fluorinated gypsum, or a combination of at least two of them.

24. The cement according to any one of claims 20 to 22, characterized in that: The gypsum is any one of natural dihydrate gypsum, natural anhydrite, hemihydrate gypsum, and desulfurized gypsum, or a combination of at least two of them.

25. The cement according to any one of claims 20 to 22, characterized in that: The cement admixture is any one of granulated blast furnace slag, fly ash, silica fume, steel slag, gasified slag, limestone, dolomite, volcanic ash mixed material or sandstone, or a combination of at least two of them.

26. The cement according to any one of claims 20 to 22, characterized in that: The raw materials also contain 0.1 to 5 parts by weight of a setting and strengthening component; the setting and strengthening component is any one of lithium hydroxide, sodium hydroxide, potassium hydroxide, lithium sulfate, sodium sulfate, potassium sulfate, aluminum sulfate, lithium carbonate, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, sodium silicate, lithium chloride, citric acid, sodium citrate or sodium gluconate, or a combination of at least two of them.

27. The cement according to claim 26, characterized in that: The setting and strengthening component is any one of lithium hydroxide, sodium hydroxide, lithium sulfate, sodium sulfate, aluminum sulfate, lithium carbonate, citric acid, sodium citrate or sodium gluconate, or a combination of at least two of them.

28. The cement according to claim 27, characterized in that: The setting and strengthening components also include any one of silicate cement, silicate cement clinker, quicklime, slaked lime, industrial calcium oxide, industrial calcium hydroxide, carbide slag, calcium oxide expansion agent, and ettringite expansion agent, or a combination of at least two thereof.

29. A method for preparing the cement according to any one of claims 20 to 28, comprising: According to the raw material ratio of cement according to any one of claims 20 to 28, the raw materials are mixed and ground together into a specific surface area of ​​200 to 800 m 2 / g of powder to obtain the cement.

30. A method for preparing the cement of any one of claims 20 to 28, comprising: According to the raw material ratio of cement described in any one of claims 20 to 28, the raw materials are mixed and ground together into a specific surface area of ​​300 to 600 m 2 / g of powder to obtain the cement.

31. A method for preparing the cement of any one of claims 20 to 28, comprising: According to the raw material ratio of cement described in any one of claims 20 to 28, the various raw materials are ground separately to a specific surface area of ​​200 to 1000 m 2 / g of powder, and then mixing to obtain the cement.

Citation Information

Patent Citations

  • Anticorrosion high-belit sulfoaluminate cement clinker and preparation method thereof, anticorrosion high-belit sulfoaluminate cement and preparation method of cement

    CN107935423A